Brincidofovir Use after Foscarnet Crystal Nephropathy in a Kidney Transplant Recipient with Multiresistant Cytomegalovirus Infection - Romain Vial; Christine Zandotti; Sophie Alain; Alexandre Decourt; Noémie Jourde-Chiche; Raj Purgus; Charleric Bornet; Laurent Daniel; Valérie Moal; Tristan Legris (Case Reports in Transplantation)
Background. Cytomegalovirus (CMV) antiviral drug resistance constitutes an increasing challenge in transplantation. Foscarnet is usually proposed when resistance for ganciclovir is suspected, but its use is limited by its nephrotoxicity. Case Presentation. We report a case of multiresistant CMV disease in a kidney transplant recipient. Foscarnet was prescribed after ganciclovir treatment failure in a patient with two mutations in the UL97 viral gene. Foscarnet induced biopsy-proven kidney crystal precipitation that resulted in severe acute transplant failure and nephrotic syndrome. Despite a large decrease in immunosuppression, CMV disease was not controlled and a salvage therapy with Brincidofovir (BCV), which is an oral lipid conjugate of cidofovir with limited nephrotoxicity, was attempted. Clinical and virological remission was observed after a 21-day course of BCV, despite mild and reversible liver toxicity. However, a new relapse could not be effectively cured by BCV due to a new mutation in the UL54 gene, which is known to confer resistance to cidofovir. A new course of foscarnet finally resulted in prolonged CMV remission. Herein, we present a review of foscarnet nephropathy cases in solid-organ transplanted patients. Conclusions. This unique case highlights the potential benefit of BCV use during resistant CMV infection, although mutations in the UL54 gene may limit its therapeutic efficacy. These findings need to be confirmed in clinical trials.